Research - Category B (ARQUISUR Revista, 2025)
Research Award - Category BThe works submitted to the ARQUISUR Research Award are those that derive from knowledge production processes, handled by teachers and/or students of the Faculties or Schools of Architecture of ARQUISUR as part of their academic activity, regardless of their source of financing, whether existed.Category B collects works produced individually or in groups by researchers trained with recognized directors in formal systems. In this category, postgraduate theses that have not been published may be accepted.
Keywords: Arquisur Awards